ORIENTASI, SIKAP DAN PERILAKU KEAGAMAAN (Studi Kasus Mahasiswa Salah Satu Perguruan Tinggi Negeri di DIY) - Sekar Ayu Aryani (Religi: Jurnal Studi Agama-agama, 2015)
This Article discusses about religious history of individual and how it effects to individual religious orientation, attitude and behavior. The discussion of this article based on a research finding of the same topic in one of state university in Yogyakarta, which focuses on how this religious history, orientation, attitude and behaviour pertains to different religious orientation of the student, namely liberal, fundamentalist and moderate orientation. It is ver y interesting when the writer finds out that in terms of religious orientation these three groups of the students prove the same type of religious orientation. And also for some aspects of religious life, the differences of them is not quite clear cut. These findings again prove that what we assume about them can not always be proved in the reality.